PSVIII-27 Flunixin meglumine does not inhibit hyperthermia induced by central administration of α-1-acid-glycoprotein, an acute phase protein, in sheep. (7th December 2018) - Daniel, J; Gregg, B; Parker, P; Waller, K; Garcia, M; Bradford, B
Abstract: Central administration of α-1-acid-glycoprotein (AGP) induces an increase in rectal temperature in ewes. To determine if AGP-induced fever in sheep is dependent on prostaglandin synthesis, non-lactating, non-pregnant, adult (≥1 yr of age) mixed breed black face ewes (n = 19) weighing 85.4 ± 19.4 (SD) kg were ovariectomized and surgically implanted with a cannula into a lateral ventricle of the brain. Ewes were kept indoors in individual pens with a 12-hour light/dark photoperiod and approximately 22–24℃. Ewes had ad libitum access to water and a diet calculated to meet their requirements. Ewes were intravenously administered either 0 (SAL) or 2.2 mg/kg BW flunixin meglumine (FLU; Prevail TM ; VetOne Meridian, ID; a cyclooxygenase inhibitory non-steroidal anti-inflammatory drug) 30 minutes prior to receiving either 0 (SAL) or 25 mg AGP ( 0.3 µg/kg BW; from bovine plasma; Sigma Aldrich Co. Saint Louis, MO) administered in 500 µL of sterile, nonpyrogenic, isotonic, 0.9% sodium chloride into the lateral ventricle. Rectal temperature was determined at -72, -48, -24, -2, 0, 2, 4, 6, 8, 12, and 24 h relative to AGP treatment. Data were analyzed using procedures for repeated measures with JMP software (version 10.0.0; SAS Inst. Inc., Cary, NC) and tested for effects of AGP treatment, FLU treatment, time, and interactions. There was an effect of central AGP administration (P = 0.0063) and AGP by time interaction (P < 0.001) on rectal temperature such that ewes treated centrally with AGP had greater rectal temperatures at 2, 4, 6, 8, and 12 h relative to ewes treated centrally with SAL. There was no effect of intravenous FLU, FLU by time interaction, FLU by AGP, or AGP by FLU by time interaction (P > 0.17). Thus, central AGP administration increases rectal temperature in sheep by a mechanism independent of prostaglandin synthesis.